Формове різноманіття Morus alba L. для озеленення: розмноження і вирощування - Vitenko, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The description of shape diversity of Morus alba L. and the results of vegetative and seed breeding are given. The principles of different ornamental forms of Morus alba L. usage in compositions are proposed.